2022
DOI: 10.3389/fpsyg.2022.844057
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Health, Quality of Life and Intrafamilial Relations – A Population-Based Survey in Germany

Abstract: The occurrence of the novel severe acute respiratory syndrome coronavirus-2 (COVID-19) at the end of 2019 comes along with many challenges. Besides worry for one’s own health and the well-being of the family, all measures applied to limit the spread of the coronavirus affected daily life. School closures, economic shutdown and contact restrictions have led to high levels of stress. The impact on health and families has been widely discussed. However, population-based data are scarce. Here, we have assessed hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…In a next step, we assessed further predictors for an increase of depressive symptoms during the pandemic, were ACEs were shown to be associated with a stronger increase in depressive symptoms. In line with this finding, ACEs were shown to be associated with a stronger decrease in quality of life and general health status during the pandemic [37,45]. Moreover, ACEs we have demonstrated that ACEs are associated with dysfunctional familiar coping strategies during the pandemic [35,36] and a higher risk for intrafamiliar problems [35,37,38].…”
Section: Discussionsupporting
confidence: 82%
“…In a next step, we assessed further predictors for an increase of depressive symptoms during the pandemic, were ACEs were shown to be associated with a stronger increase in depressive symptoms. In line with this finding, ACEs were shown to be associated with a stronger decrease in quality of life and general health status during the pandemic [37,45]. Moreover, ACEs we have demonstrated that ACEs are associated with dysfunctional familiar coping strategies during the pandemic [35,36] and a higher risk for intrafamiliar problems [35,37,38].…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, data may be only partly comparable. Nonetheless, other data also suggest a decrease in life satisfaction in the German population associated with the pandemic, as seen in a survey conducted in winter 2021/2022 with more than half of the participants in a population-based German sample reporting a decreased quality of life since the beginning of the pandemic [ 25 ]. In our sample, however, the majority reported about an equal quality of life compared with before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As described before, the answers were summarized in the categories “better”, “equal” and “worse”. [ 25 ]. To assess Depressive symptoms, the Patient Health Questionnaire-2 (PHQ2) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, individuals with more severe pre-existing psychiatric illnesses were especially vulnerable to the consequences of COVID-19 [ 5 , 6 , 7 ], particularly suicide-related ideation and behavior [ 8 , 9 , 10 ]. Children and adolescents with exposure to previous or current adverse events and traumatic experiences were also especially vulnerable for consequences of the COVID-19 crisis [ 11 ], particularly physical and psychological violence within families [ 5 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%